Differential Predictors of Suicidal Ideation and Suicide Attempts: Internalizing Disorders and Substance Use in a Clinical Sample of Adolescents. Issue 1 (2nd January 2022) - Berny, Lauren M.; Tanner-Smith, Emily E.
Abstract: Objective: Dually diagnosed adolescents are a high-risk population for experiencing suicidal thoughts and behavior. Given that research suggests risk factors for suicidal ideation and suicide attempts may be different, this study examined whether internalizing disorder severity, frequency of substance use, and the interaction between them differentiated adolescents who attempted suicide from those who ideated. Methods: Baseline data from 287 adolescents who received formal substance use disorder (SUD) treatment were used in this analysis. Major depressive disorder (MDD) and generalized anxiety disorder (GAD) severity as well as past-3 month use of alcohol, cannabis, and other illicit drugs were considered. The outcome of interest was a three-category measure of suicide risk: no reported suicidal ideation or attempts, suicidal ideation only, and suicide attempts. Results: Over half of the sample disclosed prior suicidal ideation (30.0%) or attempts (27.9%). Multinomial logistic regression models indicated more severe MDD and GAD symptomology differentiated ideators from non-suicidal adolescents, but internalizing disorder severity did not differ between ideators and attempters. Substance use frequency did not differ between suicide risk groups. MDD severity and frequency of alcohol use interacted to increase the risk of attempts, yet the effects were minimal. Instead, prior weapon violence victimization and sexual abuse were the largest differentiators between attempters and ideators. Conclusions: Findings suggest that internalizing disorder severity and prior traumatic experiences put adolescents with SUD histories at higher risk of suicidal thoughts and behaviors. Thus, integrating evidence-based suicide prevention and intervention efforts into SUD treatment is critical, particularly for dually diagnosed adolescents who meet these risk profiles. Psychotherapy and medication may help curtail the development of ideation by reducing symptoms of MDD and GAD, whereas adolescents with prior traumatic experiences may benefit from additional treatments shown to lower risk of suicide attempts.